Political Branding Edy Rahmayadi pada Kampanye Pilgub Sumatera Utara Tahun 2018 melalui Instagram - Iin Safia Banurea; Putri Maulina (Universitas Majalengka, 2022)
Political branding is a personal strategy or political organization in building a positive image in the eyes of the public. Edy Rahmayadi is one of the candidates for governor who is running for the 2018 North Sumatra gubernatorial election from the Democratic Party faction. The purpose of this study was to find out how Edy Rahmayadi's political branding in the 2018 North Sumatra gubernatorial election campaign through Instagram media. The object of this research is Instagram posts that form political branding for +- 4 months, from 15 February to 23 June 2018 with a total of 528 posts, then narrowed down to 10 post analysis units. The method used is qualitative content analysis with a direct content analysis approach based on indicators from the theory of Mitsikopolou, 2008 and the results of data induction. The results of this study indicate that Edy Ramyadi's Political branding was formed through Personalities (relationship, responsive technology and personal values), Appreance (clothes, hair style and hand signs) and Political Key Message (hope, public support, activity reports and political values). Edy Rahmayadi’s political branding is a picture of a politician who compares his personality as a different figure from othe candidate pairs through indicator namely personalit, appreance and politicak key message. This can be seen from his post describer Edy Rahmayadi as aperson who is open to all circles of society, prioritizes credibility and is open for all the citizen.